Medium term policy framework: from stabilisation to growth 1993-1995 (Government of Trinidad and Tobago Port of SpainTT, 1992)
Outlines Government's proposed macroeconomic management and sectoral policies for the period 1993-1995. Presents projections of key macroeconomic indicators including the balance of payments and external financing requirements for the period. Notes that the strategic initiatives that underpin the programme are: enhanced fiscal discipline; reliance on the private sector for incremental investment; and exports as the major source of growth and employment.
DC